SOSIALISASI PEMBERIAN FISIOTERAPI DENGAN TERAPI LATIHAN UNTUK PENCEGAHAN DAN PENGOBATAN OSTEOARTHRITIS PADA LANSIA DI SUKAGALIH GG SUKABAKTI VI RT O5 RW 03 SUKAJADI BANDUNG - Ika Rahman; Gina Indria Dewi; Rian Rusdian; Yudhistira Mahesa Putra (Insight Power (Kekuatan Wawasan), 2022)
Osteoarthritis, known as a degenerative disease, is one of the most common medical problems and causes symptoms in the elderly and middle-aged people. It occurs in people of all ethnicities, is more common in women, and is the most common cause of long-term disability in patients older than 65 years. WHO reports that 40% of the world's elderly population will suffer from Osteoarthritis, of which 80% have limited joint motion. Exercise therapy used to prevent the occurrence of Osteoarthritis is Calf Muscle Exercise and Stretching Quadriceps which aims to improve the quality of motion and reduce pain in the knee. The result of this activity is that the elderly gain knowledge on how to prevent and treat when they are exposed to Osteoarthritis or knee pain. They revealed that this socialization was very useful and quite helpful in reducing knee pain.Keywords: Osteoarthritis, Exercise Therapy, Elderly.